PICTURE-ASSISSTED SHORT STORY WRITING SKILL FOR GRADE IX D STUDENTS IN SMP NEGERI 1 JUMO (Jurnal Kreatif : Jurnal Kependidikan Dasar, 2019)
Grade IX D students in SMP Negeri 1 Jumo, Temanggung Regency got unsatisfying average score for Indonesian class, particularly short story writing lesson. The purpose of this Classroom Action Research is to find how much the impact of picture stimulus is when it is used in the short story writing skill learning on grade IX D students in SMP Negeri 1 Jumo. The population of this study was grade IX D students in SMP Negeri 1 Jumo, Temanggung Regency in semester II during 2017/2018 school year. Approximately 31 students became subjects for this study, by applying picture as teaching tool in the Indonesian learning particularly short story writing lesson. The procedure that I took during the investigation was the study I conducted onto the students during the learning process of short story writing. The study was conducted through two cycles comprising four stages, i.e.: planning, implementation, observation, and reflection. The data were collected through the students’ test results before and after applying picture-stimulus. This study was conducted through discussion and task-giving methods by asking the students to write the short story based on the picture. The study shows that the grade IX students’ skill changed in terms of writing the short stories. The grade IX students were less enthusiastic before applying picture-stimulus; only 22 (67.75%) students met the minimum mastery point. After applying picture-stimulus in the learning of short story writing, the grade IX students turned more enthusiastic, more active, thus 29 (90.63%) students met minimum mastery point. The number of the students fulfilling the criteria improved around 21.87 % or about 7 students